Periodontite em puérperas e sua relação com a prematuridade: análise de parâmetros clínicos e microbiológicos - CALIXTO , Nayra Rodrigues de Vasconcelos (2018)
The World Health Organization defines preterm birth as any live birth less than 37 weeks' gestation. Preterm birth is a public health problem, since preterm labor can complicate 10 to 15% of all pregnancies and is the main cause of neonatal morbidity and mortality. Clinical and microbiological studies have sought the relationship between Periodontal Disease (PD), periodontopathogenic bacteria and prematurity, however, the results still remain inconclusive. Thus, the objective of this study was to compare the different diagnostic criteria for periodontal disease, identifying the sensitivity and specificity among them, and to verify the influence of periodontitis diagnosis criteria on the association between PD and prematurity.As well as evaluating the presence and quantification of the periodopathies Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Treponema denticola (Td), Tannerella forshytensis (Tf) in the subgingival biofilm of puerperae with and without preterm infants, in order to estimate the possible relationship between the clinical and microbiological parameters of periodontal disease and the birth of preterm infants. A case-control study was conducted with 269 mothers of babies born in São Luís, Maranhão, Brazil, for the clinical study. For the microbiological study were 183 mothers of babies born in São Luís, Maranhão, Brazil. Mothers were divided into case group (infants gestational age <37 weeks) and control group (infants with gestational age ≥ 37 weeks). The following periodontal conditions were examined: Probing Depth, Clinical Attachement Level (CAL), Dental Plaque and Bleeding upon Probing (BOP). We used 14 criteria to diagnose Periodontal Disease to associate with prematurity, these were used of different periodontal parameters such as Probing Depth, CAL,BOP. Samples were collected from the subgingival plaque from four deeper sites up to 48 hours postpartum and were processed by Real-Time Polymerase Chain Reaction for the presence of periodontopathogens Aa, Pg, Td and Tf. An association was found between the criteria of 5 to 8, 10 and 11 with prematurity. It was also observed that there was an inverse correlation between Pg and gestational age in the control group. In logistic regression we can verify the association between the frequency of Tf and Periodontitis with prematurity. The frequency of Probing Depth ≥ 4 mm (p = 0.002) and the frequency of CAL ≥ 5 mm (p = 0.002) were also observed as clinical parameters related to prematurity. It was concluded that the criteria of PD that use Probing Depth ≥ 4 mm and CAL ≥ 3 mm in 2 or more teeth, and preferably with BOP at the same site, seem to be more consistent when detecting an association between periodontitis and prematurity. And there was a significant association between the frequency of Tf and periodontitis with prematurity.